«Calma», de Óscar L. Figueruelo Burrieza (Castilla. Estudios de Literatura, 2021)
Óscar L. Figueruelo (1972) makes his debut as a novelist with Calma, a story about fear of the unknown set in a region of small towns and its surrounding countryside.